STUDI FENOMENOLOGI UPAYA KELUARGA DALAM PERKEMBANGAN ANAK BERKEBUTUHAN KHUSUS DI SPECIAL KIDS DAN THERAPY PEKANBARU - Harahap , Putri Khadijah; Gumayesty, Yeyen; Priwahyuni, Yuyun; Kursani, Elmia (LPPM Universitas Awal Bros, 2025)
Developmental disorders are failure to grow and develop when a child is born at term but experiences disabilities or even before birth so that they are different from normal children in general. This research aims to support families in the development of children with special needs in 2023. This research uses a qualitative type with a phenomenological approach and was conducted at Special Kids and Therapy Pekanbaru in May-August 2023. The informants for this research were 8 people, namely parents of children with special needs as main informant, other families of children with special needs as key informants, therapists as supporting informants. Data were collected using observation and in-depth interviews and processed using the triangulation method. The results of the research show that it is known that the development of each type of child with physical impairment, speech impairment and hearing impairment is not yet optimal, the fulfillment of nutritious food intake is not yet balanced due to irregular eating patterns, providing stimulation at home and in therapy places by inviting children to play and study, therapy For children with special needs, it has been carried out according to the therapist's recommendations, the parents have implemented parenting patterns using a democratic parenting style. The conclusion of this research is that the provision of nutritious food intake is not balanced because children are picky eaters so that children's development is not optimal.